Relaxation of dislocation structures under ultrasonic influence. (January 2019) - Bachurin, D.V.; Murzaev, R.T.; Nazarov, A.A.
Abstract: Relaxation of disordered dislocation structures under ultrasonic influence in a two-dimensional square-shaped grain is investigated using the discrete-dislocation approach. The model grain contains three non-parallel glide systems inclined at an angle of 60° to each other. Non-equilibrium grain boundary state is modeled by means of a mesodefect located at the corners of the square-shaped grain. The stress fields of this mesodefect are described by those of a wedge junction disclination quadrupole. Oscillating stresses result in a rearrangement of lattice dislocations and their gliding towards the grain boundaries. This process is accompanied by a reduction of internal stress fields and cancellation of the wedge disclination quadrupole. The presence of non-parallel glide systems leads to a formation of Lomer–Cottrell locks, when two or more dislocations belonging to different systems meet at one point. Influence of the amplitude of ultrasonic treatment on the relaxation of dislocation structures is studied. Ultrasound of low amplitudes results in a formation of dislocation walls in the grain interior, while at higher amplitudes the dislocation substructure is destroyed and majority of the lattice dislocations are absorbed by the grain boundaries. The model predicts an existence of optimal values of the ultrasound amplitudes, at which the maximum reduction of internal stresses can be achieved. Dependence of the relaxation of disordered dislocation structures on the grain size is explored. The results obtained are consistent with those of previous theoretical and experimental studies.